Access to medicines for the treatment of chronic diseases in Chile: qualitative analysis of perceived patient barriers and facilitators in five regions of the country - Carla Castillo-Laborde; Isabel Matute; Ximena Sgombich; Daniel Jofré (BMC Health Services Research)
Abstract Background Access to medicines is one of the most serious public health problems globally, and Chile is not an exception. The aim of this study was to explore patients' perceptions, beneficiaries of both public and private health sectors, of barriers and facilitators in access to medicines in general, and those associated with the treatment of diabetes, dyslipidemia and hypertension. Methods Ten focus groups of patients with these diseases, diagnosed for at least six months and with prescribed medication, were carried out in five regions of Chile: Arica (north), Aysén (south), and Valparaíso, Metropolitan, and Maule (center). Results The experience of access to medicines is determined by the insurance system, the experience of care with public or private providers, and geographical-administrative difference between capital and other regions. Beneficiaries of public sector value territorial coverage of primary care, which guarantees access in isolated areas and, despite their greater socioeconomic vulnerability, perceive greater protection in access (access conditions, delivery reliability and adherence to pharmacological treatment). The main problem observed is the financing of treatments not covered by the system. Beneficiaries of private sector perceive that they have access to medicines of better quality than those provided free of charge by public sector, but raise fears associated with the inability to afford them and distrust in the market process. Regarding the type of provider, public sector shows greater capacity for user loyalty, which is expressed in regular visits and follow-up, unlike discontinuous examinations among private sector beneficiaries. Conclusions Different access conditions both at the territorial level and in the health subsystems are evident. It is necessary to make progress in addressing the problem of access to medicines in a comprehensive manner.